Study on the Dose and Exposure Characteristics of the Automatic Optimization Parameter Mode in Mammography - Moon, Young-Ju; Jung, Hong-Ryang; Lim, Woo-Taek (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of study was to provide useful information on the choice of the AOP mode of units that can improve the quality of breast images and reduce exposure dose by analyzing the dose and exposure characteristics of the AOP mode used in the mammography unit of the digital system.Methods/Statistical analysis: The equipment used in the experiment is GE’s Senographe Pristna and Hologic's Selenia Dimensions. The phantom used Polymethylmethacrylate phantoms and ACR phantom for the evaluation each according to the automatic exposure control of parameters mode for each equipment to evaluate the average dose. Statistical analysis was performed using one-way ANOVA, and post-hoc was performed using the Tukey method. The statistically significant range was set to (p